The Sci-Fi Brain: Narratives in Neuroscience and Popular Culture - Alftberg, Åsa; Bengtsen, Peter (Culture Unbound, 2018)
The connection between neuroscience, popular media and lay perceptions of the brain involves the framing of complex scientific processes and results through familiar cultural narratives and metaphors. Such narratives are often built on the premise that neuroscience, with the help of powerful new technologies, will finally solve the mysteries of brain and mind, consciousness and morality. At the same time, popular culture—especially the science fiction genre—tends to focus on worst case scenarios of the implementation of technology. This article explores cultural narratives of what the brain is and how it functions in two different contexts—among neuroscientists and within popular culture. In particular, narratives about technology and the malleable brain as well as the notion of the mad scientist are studied. The article explores how these narratives are presented and used in popular culture and how neuroscientists relate to the narratives when describing their work. There is a contrast, but also a blurring of boundaries, between actual research carried out and the fictional portrayals of scientists constructing, or altering, fully functional brains. To some extent, the narratives serve as a background for the public’s understanding of, and attitude towards, neuroscience—something that must be taken into consideration when dealing with the therapeutic treatment of patients. The narratives of neuroscience in popular culture are to a certain degree shaped by actual scientific practices and findings, but neuroscience is also influenced by laypeople’s perceptions, which often have their roots in the narratives of popular culture.